Dwelling in the Daily Life of a Place - Maddock, Sherry (Missiology, 2010)
In this time of unprecedented cultural change. Western Christians must be willing to take the long view of mission work, dwelling in the daily life of a place and engaging in the slow, faithful work of our Reconciling God. Living in community, we are enabled to grow in our relationships with God, with each other, and with the place around us. This relational growth occurs in simple, local ways, face to face, one relationship at a time.